Full-Field Strain Uncertainties and Residuals at the Cartilage-Bone Interface in Unstained Tissues Using Propagation-Based Phase-Contrast XCT and Digital Volume Correlation - Tozzi, Gianluca (Materials (Basel), 2020)
A deeper understanding of the cartilage-bone mechanics is fundamental to unravel onset and progression of osteoarthritis, enabling better diagnosis and treatment. The aim of this study is therefore to explore the capability of X-ray computed (XCT) phase-contrast imaging in a lab-based system to enable digital volume correlation (DVC) measurements of unstained cartilage-bone plugs from healthy adult bovines. DVC strain uncertainties were computed for both articular cartilage and mineralized tissue (calcified cartilage and subchondral bone) in the specimens at increasing propagation distances, ranging from absorption up to four times (4× such effective distance. In addition, a process of dehydration and rehydration was proposed to improve feature recognition in XCT of articular cartilage and mechanical properties of this tissue during the process were assessed via micromechanical probing (indentation), which was also used to determine the effect of long X-ray exposure. Finally, full-field strain from DVC was computed to quantify residual strain distribution at the cartilage-bone interface following unconfined compression test (ex situ). It was found that enhanced gray-scale feature recognition at the cartilage-bone interface was achieved using phase-contrast, resulting in reduced DVC strain uncertainties compared to absorption. Residual strains up to ~7000 µε in the articular cartilage were transferred to subchondral bone via the calcified cartilage and micromechanics revealed the predominant effect of long phase-contrast X-ray exposure in reducing both stiffness and hardness of the articular cartilage. The results of this study will pave the way for further development and refinement of the techniques, improving XCT-based strain measurements in cartilage-bone and other soft-hard tissue interfaces.